Applications of Landsat-8 Data: a Survey - Ridwan, M. A.; Radzi, N. A. M.; Ahmad, W. S. H. M. W.; Mustafa, I. S.; Din, N. M.; Jalil, Y. E.; Isa, A. M.; Othman, N. S.; Zaki, W. M. D. W. (International Journal of Engineering and Technology, 2018)
Landsat 8 was launched in 2013 by the National Aeronautics and Space Administration (NASA). On board of the Landsat 8 is the Operational Land Imager (OLI) and Thermal Infrared Sensor (TIRS). Data for visible, panchromatic band, short-wave infrared spectral bands are collected by the OLI while TIRS collect images in the thermal region. As data for Landsat 8 is available to be used for public, researchers have utilized the data for numerous applications. However, to the best of our knowledge, there is yet a review paper on the various applications of Landsat 8 data. Hence, this paper presented an innovative survey on Landsat 8 data in the application of agriculture and forestry, land use and mapping, geology, hydrology, coastal resources and environmental monitoring. The potential of utilizing Landsat 8 data for power utility companies is also discussed in this paper. As Landsat 8 data is predicted to be available for more years to come, this paper provides insight for researchers to utilize the data better for their research.
Keywords: Landsat 8; remote sensing; review; survey; power related